INTERCULTURAL COMMUNICATION IN TEACHING LANGUAGES - Norbekova, Rano (Журнал иностранных языков и лингвистики, 2023)
The aim of this article is the explore, review and critique the multi-disciplinary literature on the concept of culture shock which is the unexpected and often negative reaction of people to new environments. Whilst it touches on a wider literature on such things as intercultural contact and competence and the process of adaptation and adjustment to new cultures, it focuses on the short-term reaction of travellers. Its aim is primarily educational, aimed specifically at travellers and educators.